Characteristics of antimuscarinic responders versus suboptimal responders in a randomized clinical trial of patients with overactive bladder symptoms. (3rd October 2017) - Grenabo, Lars; Herschorn, Sender; Kaplan, Steven A.; Cardozo, Linda; Scholfield, David; Arumi, Daniel; Carlsson, Martin; Chapman, Douglass; Ntanios, Fady
Abstract: Objective: To assess the characteristics of tolterodine extended-release (ER) 4 mg responders and suboptimal responders (≤50% decrease in UUI episodes/24 h) among patients with overactive bladder (OAB), including urgency urinary incontinence (UUI), and identify predictors of a >50% UUI response with fesoterodine 8 mg in tolterodine suboptimal responders. Methods: Adult patients with OAB symptoms for ≥6 months and ≥8 micturitions, and ≥2 and <15 UUI episodes/24 h at week −2 received open-label tolterodine ER 4 mg during a 2 week run-in. Suboptimal responders after tolterodine treatment (week 0) were randomized to fesoterodine (4 mg for 1 week, 8 mg for weeks 2–12) or placebo once daily. Post-hoc analyses compared the percentage change from week −2 to week 0 in UUI episodes/24 h in tolterodine responders versus suboptimal responders and identified significant predictors of a UUI response at week 12 with fesoterodine 8 mg among tolterodine suboptimal responders. Results: Of 897 patients, 610 (68%) were UUI suboptimal responders during the run-in period. UUI episodes/24 h at week −2 were similar in tolterodine responders and suboptimal responders (4.2 vs. 4.3), but responders showed a significantly greater median percentage decrease in UUI episodes/24 h after tolterodine treatment at week 0 (80.0% versus 15.3%; p < .0001). During double-blind treatment, the percentage of patients with a UUI response at week 12 was significantly greater with fesoterodine (69.9%) than placebo (57.0%; p = .0027). Fesoterodine (vs. placebo), no previous antimuscarinic use before tolterodine run-in, and less UUI severity at baseline were significant predictors of a UUI response. Conclusions: For patients with OAB, including UUI, who were treated initially with tolterodine and showed a suboptimal UUI response, nearly 70% demonstrated a UUI response with second-line fesoterodine 8 mg. No antimuscarinic use before tolterodine and fewer baseline UUI episodes were significant predictors of a UUI response with fesoterodine.